Exploring Suitability of Salsola imbricata (Fetid Saltwort) for Salinity and Drought Conditions: A Step Toward Sustainable Landscaping Under Changing Climate - Alam, Hasnain; Zamin, Muhammad; Adnan, Muhammad; Shah, Adnan Noor; Alharby, Hesham F.; Bamagoos, Atif A.; Alabdallah, Nadiyah M.; Alzahrani, Saleha S.; Alharbi, Basmah M.; Saud, Shah; Hassan, Shah; Fahad, Shah (Frontiers in Plant Science, 2022)
In context of the climate change major abiotic stresses faced by plants include salt and drought stress. Though, plants have similar physiological mechanisms to cope with salt and drought stress. The physiological and biochemical response of native plants to the combined application of salinity and drought stress is still not well understood. Thus, to investigate the combined effect of salinity and drought stress an experiment was conducted on Salsola imbricata with four levels of salinity and four drought intensities under the arid climatic conditions. The experiment was conducted in a randomized complete block design with a split-plot arrangement replicated three times. S. imbricata had been found resistant to different levels individual and combined salt and drought stress. S. imbricata survived till end of experiment. Salt and water stress did not show any significant effects on shoot weight, shoot length and root length. Drought stress affected the photosynthetic rate, ion uptake and leaf water potential. However, salt stress helped to counter this effect of drought stress. Thus, drought stress did not affect plant growth, photosynthesis rate and ion uptake when combined with salt stress. Increased Na+ and Cl- uptake under salt stress helped in osmotic adjustment. Therefore, Leaf water potential (LWP) decreased with increasing salt stress from 5 dSm-1 until 15 dSm-1 and increased again at 20 dSm-1. At lower salt stress ABA and proline content declined with increasing drought stress. However, at higher salt stress ABA content increased with increasing the drought stress. In conclusion salt stress had been found to have a protective role to drought stress for S. imbricata. S. imbricata utilized inorganic ion for osmotic adjustment at lower salinity stress but also accumulate organic solutes to balance the osmotic pressure of the ions in the vacuole under combine stress conditions. Due to the physical lush green appearance and less maintenance requirements S. imbricata can be recommended as a native substitute in landscaping under salt and drought stress conditions